Dispersal by passionvine hopper (Scolypopa australis) adults - Tomkins, A.R; Wilson, D.J.; Thomson, C.; Allison, P. (New Zealand Plant Protection, 2000)
Passionvine hopper (Scolypopa australis) (PVH) is a serious pest in some Bay of Plenty kiwifruit orchards with large numbers of PVH adults flying in from adjacent scrub A series of field experiments investigated their dispersal abilities Adult PVH released into an open area were recaptured on sticky traps up to 70 m downwind two hours later When released inside a kiwifruit orchard PVH gradually dispersed throughout a block of vines Sticky traps at different heights along an orchard border caught PVH up to 2 m above ground Different shaped (rectangle square or triangle) traps caught similar numbers of PVH adults